2014
DOI: 10.1155/2014/263548
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure Refinement, and Electrical Conductivity of Pb(8−x)Na2Smx(VO4)6O(x/2)

Abstract: Solid solutions of Pb(8−x)Na2Smx(VO4)6O(x/2)were studied using X-ray diffraction analysis including Rietveld refinement and scanning electron microscopy and by measuring their electrical conductivity. Crystal structure of the solid solutions was refined and the solubility region0≤x≤0.2was determined for samarium substitution for lead under the scheme2Pb2++□→2Sm3++O2-. The influence of degree of substitution on the electrical conductivity of solid solutions was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…It should be noted that the structure of lead-containing apatites contains two structurally non-equivalent cation sites Pb1(4 f ) and Pb2(6h) [11,[31][32][33][34]. The authors of [34] showed that La atoms in the apatite Pb 8 La 2 (GeO 4 ) 4 (VO 4 ) 2 after lead substitution by lanthanum are mainly located at site Pb1, despite the fact that the effective charge of La 3+ is greater than the effective charge of Pb 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the structure of lead-containing apatites contains two structurally non-equivalent cation sites Pb1(4 f ) and Pb2(6h) [11,[31][32][33][34]. The authors of [34] showed that La atoms in the apatite Pb 8 La 2 (GeO 4 ) 4 (VO 4 ) 2 after lead substitution by lanthanum are mainly located at site Pb1, despite the fact that the effective charge of La 3+ is greater than the effective charge of Pb 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…The interest in such compounds is conditioned by the unique properties which are of applied value; they can be used as biomaterials, phosphors, sensors, laser and fluorescent materials, organic synthesis catalysts [1][2][3][4][5][6][7], in acousto-optic devices, in medicine, power industry, oil refining, environment protection [8], for radioactive waste disposal [9]. A distinctive feature of compounds with the apatite structure is the possibility of substitution of certain structural units by others without a considerable change of the structure [3,[10][11][12][13][14][15]. Such a substitution allows both for changing the properties of the already known compounds with the apatite structure and for making new materials [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Заметим, что в структуре свинецсодержащих апатитов имеются две структурно-неэквивалентные катионные позиции Pb1(4 f ) и Pb2(6h) [11,[31][32][33][34]. B работе [34] показано, что при замещении свинца лантаном в апатите состава Pb 8 La 2 (GeO 4 ) 4 (VO 4 ) 2 атомы La располагаются в основном в позиции Pb1, несмотря на то, что эффективный заряд La 3+ больше, чем эффективный заряд Pb 2+ .…”
Section: результаты и их обсуждениеunclassified
“…Интерес к таким соединениям обусловлен наличием уникальных свойств, имеющих прикладную ценность, что позволяет использовать их в качестве биоматериалов, люминофоров, сенсоров, лазерных и флуоресцентных материалов, катализаторов органического синтеза [1][2][3][4][5][6][7], в акустооптических устройствах, в медицине, энергетике, нефтепереработке, охране окружающей среды [8], для утилизации радиоактивных отходов [9]. Отличительной особенностью соединений со структурой апатита является возможность замещения одних структурных единиц другими без существенного изменения структуры [3,[10][11][12][13][14][15]. Такое замещение дает возможность как изменять свойства уже известных соединений со структурой апатита, так и получать новые материалы [16,17].…”
Section: Introductionunclassified
“…Апатиты, обладая уникальными физико-химическими свой ствами, уже в течение длительного времени привлекают к себе внимание исследователей и практиков [1][2][3][4][5][6][7][8][9][10]. Они используются в качестве биоматериалов, лазерных, люминесцентных и оптических материалов [3,11].…”
Section: Introductionunclassified